A Controversial, But Welcome New Perspective on Structural Racism in Dutch Society (KULT_online, 2018)
In White Innocence: Paradoxes of Colonialism and Race (2016), Gloria Wekker studies the white Dutch sense of self, which to her revolves around a self-proclaimed innocence: i.e. the claim that The Netherlands is free of racism. Whenever this identity is questioned, Wekker sees a tendency in society to aggressively defend this sense of innocence. Such protective mechanisms, paradoxically, often come in the shape of racism. Throughout five chapters, she discusses such paradoxical racism, as it appears in different layers of society: the national media, bureaucratic organizations, academia, political rhetoric, and national culture. Rather than to take a stance in the discussions she analyzes, she works on a meta-level, studying the recurring factors of such discussions that in turn lead to structural racism. Her eclectic method of combining theoretical discussions with personal anecdotes, with hypothetical ‘what if…’ scenarios, and with practical proposals for societal change, sometimes runs the risk of obscuring her argumentation. Nevertheless, her approach is much needed in a debate landscape that nowadays so easily tends to escalate and polarize.